The dynamics of text and framing phenomena historical approaches to paratext and metadiscourse in English - Peikola, Matti; Bös, Birte, 1974- (Pragmatics & beyond ;, 2020)
"This volume explores the complex relations of texts and their contextualising elements, drawing particularly on the notions of paratext, metadiscourse and framing. It aims at developing a more comprehensive historical understanding of these phenomena, covering a wide time span, from Old English to the 20th century, in a range of historical genres and, contexts of text production, mediation and consumption. However, more fundamentally, it also seeks to expand our conception of text and the communicative 'spaces' surrounding them, and probe the explanatory potential of the concepts under investigation. Though essentially rooted in historical linguistics and philology, the twelve contributions of this volume also are open to insights from other disciplines (such as medieval manuscript studies and bibliography, but also information studies, marketing studies, and even digital electronics), and thus tackle opportunities and challenges in researching the dynamics of text and framing phenomena in a historical perspective"--